2009
DOI: 10.1021/ja907867b
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical Scanning Tunneling Spectroscopy of Redox-Active Molecules Bound by Au−C Bonds

Abstract: A comparison of the electrochemical gating of molecular conduction by a redox [Os(bipyridine)(pyridine)Cl] complex tethered to Au(111) with two different metal-molecule junctions in a scanning tunneling microscope nanogap is presented. The same redox molecular structure was tethered by mercaptobenzoic acid or reduction of the aryldiazonium salt of p-aminobenzoic acid, resulting in a Au-S or Au-C bond, respectively. A two-step electron-transfer mechanism with vibrational relaxation of the redox molecule is appa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
54
1

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(59 citation statements)
references
References 34 publications
3
54
1
Order By: Relevance
“…Our group has contributed with similar studies of Au-C and Au-S short-tethered Os bipyridine-pyridine chloride complex in the STM Btunneling gap^configuration with similar sequential two-step ET mechanism between the molecule and the tip and substrate metal contacts with partial vibration relaxation [23]. The Os[(bpy) 2 (PyCH 2 NH 2 CO-]ClO 4 attached to Au electrodes by self-assembling mercapto alkanoic or mercaptobenzoic acids with post-functionalization via amide formation with primary amines in the metal complex has been reported by Ricci et al [23][24][25][26][27][28].…”
Section: (Os Andmentioning
confidence: 88%
See 1 more Smart Citation
“…Our group has contributed with similar studies of Au-C and Au-S short-tethered Os bipyridine-pyridine chloride complex in the STM Btunneling gap^configuration with similar sequential two-step ET mechanism between the molecule and the tip and substrate metal contacts with partial vibration relaxation [23]. The Os[(bpy) 2 (PyCH 2 NH 2 CO-]ClO 4 attached to Au electrodes by self-assembling mercapto alkanoic or mercaptobenzoic acids with post-functionalization via amide formation with primary amines in the metal complex has been reported by Ricci et al [23][24][25][26][27][28].…”
Section: (Os Andmentioning
confidence: 88%
“…The Os[(bpy) 2 (PyCH 2 NH 2 CO-]ClO 4 attached to Au electrodes by self-assembling mercapto alkanoic or mercaptobenzoic acids with post-functionalization via amide formation with primary amines in the metal complex has been reported by Ricci et al [23][24][25][26][27][28].…”
Section: (Os Andmentioning
confidence: 99%
“…21 Electrochemically gated molecular junctions have also been realized to achieve conductivity modulation of organic and metal complexes. 22,23 For example, with a ferrocene unit terminated with two cysteamine groups, Tao et al showed that with an electrochemical gate set at 0.6 V the current increases by one order of magnitude. This gate effect is ascribed to oxidation of the molecule when its HOMO is raised to the Fermi level of the electrode.…”
Section: Functional Molecular Junctions With Metal Complexesmentioning
confidence: 99%
“…Conductance switching in molecular junctions has been demonstrated previously using various means including light, 1, 2 bias pulses, 3 electrostatic-, 4,5 and electrochemical gating. 6,7 The concept of "electrochemical gating" which provides the opportunity to overcome the technical challenges of incorporating a gate electrode in a solid-state molecular device, has been employed in electrochemically active molecular systems, including viologens, [8][9][10] oligoaniline, 11 ferrocene, [12][13][14] transition metal complexes, 7,15,16 perylenebisimides, [17][18][19] redox-active proteins, 20,21 quinones 22,23 and tetrathiafulvalene, 24 as well as redox-inactive molecules. 25 In the case of redox-inactive molecules, or more generally when the electrode potential does not overlap with the molecule's redox potential, the effect of the gate is simply to shift the molecular levels up or down in energy relative to the Fermi level.…”
mentioning
confidence: 99%